New superacid ZrO2–SiO2–Al2O3 oxide and its activity in the oligomerization of tetrahydrofuran - Inshina, E. I.; Telbiz, G. M.; Brei, V. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Strong acidic mixed ZrO2−SiO2−Al2O3 oxide has been synthesized by the sol-gel method. It was found that superacid (H0=−14,52) sites are formed at the following ion content: 12≤Zr4+≤39, 48≤Si4+≤72, 3≤Al3+≤31%(at.). According to the IR spectra of adsorbed pyridine and deuterated acetonitrile, the L- and B-sites are on the surface of ZrO2−SiO2−Al2O3. The generation of superacidity in the ZrO2−SiO2−Al2O3 matrix could be explained by the formation of coordination-unsaturated Zr4+ ions as strong Lewis acid sites. It was shown that ZrO2−SiO2−Al2O3 efficiently catalyzes the oligomerization of tetrahydrofuran in the presence of acetic anhydride with 68% yield of polytetramethyleneoxide acetate (Mn=510) at 40 ºC.